PENGARUH KOMUNIKASI DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA CV. HALUAN TEKNIK TANGERANG - Rizki Al Badary; Laura Komala (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the effect of communication and teamwork on employee performance at CV. Haluan Teknik Tangerang. The research method used was quantitative with data collection techniques through questionnaires. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing using the SPSS program. The results showed that communication had a positive and significant effect on employee performance with the regression equation Y = 1.985 + 0.955X₁, a correlation value of 0.918, and a coefficient of determination of 84.3%. The t-test results showed that t count > t table (16.532 > 1.675) with a significance value of 0.000 < 0.05. Teamwork also had a positive and significant effect on employee performance with the regression equation Y = 5.396 + 0.862X₂, a correlation value of 0.887, and a coefficient of determination of 78.7%. The t-test results showed that t count > t table (13.723 > 1.675) with a significance value of 0.000 < 0.05. Simultaneously, communication and teamwork had a significant effect on employee performance with the regression equation Y = 1.620 + 0.673X₁ + 0.290X₂, a correlation value of 0.926, and a coefficient of determination of 85.8%. The F-test results showed that F count > F table (150.857 > 3.18) with a significance value of 0.000 < 0.05.